Characteristics of nutrients and phytoplankton productivity in Guangdong coastal regions, South China. Issue 1 (15th December 2016) - Zhang, Ling; Shi, Zhen; Zhang, Jingping; Jiang, Zhijian; Huang, Liangmin; Huang, Xiaoping
Abstract: In order to evaluate the levels and the influence on phytoplankton productivity of dissolved nutrients, concentrations and distribution of N, P and Si were studied in coastal areas profoundly influenced by human activities in Guangdong Province, South China. Generally, concentrations of dissolved inorganic nitrogen were high in wet periods because of the inputs from strong seasonal land runoff. Si and P concentrations were generally low in summer due to the consumption by phytoplankton growth. Dissolved organic N and P were important in study area. Chl a and primary productivity (PP) were relatively high and showed seasonal and geographical variations. Concentrations of Chl a were the highest in summer, and the high water temperature and sufficient illumination accelerated the growth of phytoplankton, especially in surface water. Additionally, water stratification in summer decreased mixed layer depth and trapped PP in upper layer. Highlights: Runoff contributed more to nutrients, which varied following regional development. Dissolved organic N and P were important and worth of further study. Water stratification was an important reason for high Chl a and PP levels in summer. High Si/P and N/P ratios and low P levels indicated the potential P limitation.